Mosquées algériennes et expérimentations architecturales. Une législation en cours - Dalila Senhadji (L’Année du Maghreb)
The question of the architecture of the mosques supported by committees or associations in Oran arises with insistence as the mosque models question the classic architectural models in the building of these places of worship. It is through the eyes of an architect that the underlying problem of this article is posed. We had already discussed it in a previously published article, but today new legislation has been promulgated to fill in the gaps in the previous one. It is the subject of this article. We will analyze the process of designing and building the place of worship. This includes identifying the actors involved and the project manager, decrypting the administrative procedures Department of Religious Affairs, to understand the architectural choices.